Andrographolide prevented toluene diisocyanate-induced occupational asthma and aberrant airway E-cadherin distribution via p38 MAPK-dependent Nrf2 induction. (December 2018) - Sulaiman, Ibrahim; Tan, Khaishin; Mohtarrudin, Norhafizah; Lim, Jonathan Chee Woei; Stanslas, Johnson
Abstract: Toluene diisocyanate (TDI) is a major cause of chemical-induced occupational asthma, which contributes about 15% of global asthma burden. Resistance and compounded side effects associated with the use of corticosteroid in asthma necessitate the search for alternative drugs. Andrographolide (AGP), a naturally occurring diterpene lactone is known to exhibit various bioactivities. Its ability to ameliorate cardinal features of allergic asthma was previously suggested in an eosinophilic asthma endotype. However, its potential antiasthma activity and mechanism of action in a neutrophilic occupational asthma model, as well as its effect on epithelial dysfunction remain unknown. BALB/c mice were dermally sensitised with 0.3% TDI or acetone olive oil (AOO) vehicle on day 1 and 8, followed by 0.1% TDI intranasal challenge on days 15, 18 and 21. Endpoints were evaluated via bronchoalveolar lavage fluid (BALF) cell analysis, 2′, 7′-dichlorofluorescein diacetate (DCFDA) assays, immunoblotting, immunohistochemistry and methacholine challenge test. Decreases in total and differential leukocyte counts of BALF were recorded in AGP-treated animals. The compound dose-dependently reduced intracellular de-esterification of DCFDA, thus suggesting AGP's potential to inhibit intracellular reactive oxygen species (ROS). Mechanistically, the treatment prevented TDI-induced aberrant E-cadherin distribution and restored airway epithelial β-catenin at cell to cell contact site. Furthermore, AGP ameliorated TDI induced pulmonary collagen deposition. In addition, the treatment significantly upregulated pulmonary HO-1, Nrf2 and phospho-p38 levels. Airway hyperresponsiveness was markedly suppressed among AGP-treated animals. Collectively, these findings suggest AGP's protective function against TDI-induced airway epithelial barrier dysfunction and oxidative lung damage possibly through the upregulation of adherence junction proteins and the activation of p38/Nrf2 signalling. This study elucidates the therapeutic potential of AGP in the control and management of chemical-induced allergic asthma. To the best of our knowledge, the potential anti-asthma activity of AGP in TDI-induced occupational asthma has not been reported previously. Graphical abstract: